STRATEGI PENGEMBANGAN PERTANIAN PADI SAWAH DI DESA TALLE KECAMATAN SINJAI SELATAN - Syamsiah, Syamsiah; Astaman, Putra; Nurdin, Fadilah; Aisyah, Megawati (Jurnal Riset Multidisiplin Agrisosco, 2025)
Analysis of strategies related to the development of lowland rice farming in Talle Village, South Sinjai Subdistrict, Sinjai Regency. Supervised by Fadilah Nurdin. and Megawati. This study aims to formulate a development strategy for lowland rice farming in Talle Village, South Sinjai Subdistrict, Sinjai Regency. A quantitative descriptive approach was used, employing SWOT (Strengths, Weaknesses, Opportunities, Threats) analysis, the Internal-External (IE) Matrix, and the Quantitative Strategic Planning Matrix (QSPM). The analysis results revealed that the main internal strengths include the availability of quality seeds, sufficient labor, and farmers' extensive experience in rice cultivation. Meanwhile, the main internal weaknesses are limited capital and restricted land ownership. From the external environment, potential opportunities lie in the high market demand, strong support from farmer groups, and access to agricultural technology, whereas the main threats are climate change, pest attacks, and the conversion of agricultural land to non-agricultural use. The study concludes that the recommended development strategy is to leverage internal strengths and external opportunities by enhancing farmers' capacity, strengthening farmer institutions, using high-quality seeds, and adopting appropriate technology in both cultivation and post-harvest handling. This strategy is expected to sustainably improve the productivity and income of rice farmers in Talle Village.